The Influence Of Gender Stereotypes On Career Interests Of Children In Grades 1 And 5, With Gender Role And Academic Self-Efficacy As Mediators, And Grade In School As A Moderator - Ayriza, Yulia (2013)
In Indonesia, especially in the traditional Javanese society which is well known for their adherence to patriarchal customs, children have been socialized with gender stereotypes that are deeply internalized in their gender roles. These gender roles in many ways have restricted children’s potentials, especially those of girls. The study was designed to examine the influence of environmental gender stereotypes on children’s career interests as mediated by their gender role and academic self-efficacy. Based on Bandura’s model of triadic reciprocal interaction, fathers’, teachers’, and peers’ gender stereotypes were considered environmental factors; gender role and academic self-efficacy as personal factors; and level and range of career interests as behavioral factors. This study also compared children’s gender-related development in each variable, with children’s grade in school as a moderator. 387 first graders and 375 fifth graders in Yogyakarta, Indonesia were involved in this study. Besides, 762 children’s fathers, 79 homeroom teachers, and 762 peers were also involved. Liben and Bigler’s OAT-AM, COAT-AM, and COAT-PM (Liben et al., 2002) were modified and used to identify gender stereotypes and gender role, while academic self-efficacy and career interests were measured using self-constructed scales. In filling out the scales, the students were guided by well-trained research assistants, each standing by two children for the first graders and by ten children for the fifth graders. The results showed that fathers’ and teachers’ gender stereotypes significantly influenced children’s feminine gender role but not their masculine gender role.